Pengaruh Pengeluaran Konsumsi Rumah Tangga, Investasi Swasta dan Belanja langsung Pemerintah Daerah Terhadap Pertumbuhan Ekonomi di Kabupaten Lombok Timur Tahun 2001-2017 - Padli Padli; Hailuddin Hailuddin; Wahyunadi Wahyunadi (P4M STIE Putra Bangsa, 2020)
This study aims to analyze household consumption expenditure, private investment and direct local government expenditure on economic growth in East Lombok Regency and analyze which variables have a dominant influence on economic growth in East Lombok Regency. This research is a type of causal research with quantitative methods using multiple linear regression analysis methods. The dependent variable in this study is economic growth, household consumption expenditure, private investment and direct regional government expenditure as the independent variable. The results showed that household consumption expenditure and private investment had no significant effect on economic growth. While the local government direct expenditure variable has a significant effect on economic growth. The local government direct expenditure variable has a dominant influence on economic growth, while the variable with the smallest influence on economic growth is the household consumption variable.